Factores socio-culturales y su relación con el nivel de conocimiento de lactancia materna exclusiva de madres de niños de 0 – 6 meses de edad atendidas en el Hospital II – 2 Minsa -Tarapoto Abril – Julio 2013´ - Rojas Becerra, Verónica Milagros (2013)
The present investigation was conducted inmothers of children0-6months oldat Hospital MINSAII-2TARAPOTO in the period (April-July 2013). The aimof thisresearch was todetermine therelationship betweensocio-cultural factorsandthelevelofknowledgeaboutexclusive breastfeeding. It was necessary toidentifythe sociocultural factorsof mothersof children0-6months of age, thendetermined the levelof knowledge aboutexclusive breastfeeding andfinallyidentified thesignificantdimensionsociocultural factorsof mothersof childrenof0-6months age. By applyingthe instrumentwas determined that thestudy group hadan average of41.80points,ranking theMiddleKnowledgelevel. Between the level ofknowledge andsocio - cultural factorsfound thatstatistically significant relationshipbetween age andknowledgelevel(X2 =16.309, p = 0.01200000). In applyingthechi-squarestatistical test, we found that there isstatistically significant relationship betweenthe level of educationand level ofknowledge (X2 = 16.309, p = 0.01200000).